ã€Šå¤ç”¸æ—¥æŠ¥ã€‹æ±‰è¯å¤–æ¥è¯ç ”ç©¶ - Qadriani, Nanda Lailatul; Thamrin, Lily; Tjen, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
ä¸ºäº†ç»™å¤§å®¶æä¾›å‚è€ƒä¸Žå¯¹æ¥è‡ªå°å°¼è¯çš„æ±‰è¯å¤–æ¥è¯åšåˆæ¥çš„ç ”ç©¶ï¼Œæœ¬æ–‡ä»¥ã€Šå¤ç”¸æ—¥æŠ¥ã€‹2013å¹´9æœˆåˆ°2014å¹´2æœˆæ¥è‡ªå°å°¼è¯çš„æ±‰è¯å¤–æ¥è¯ä¸ºç ”ç©¶å¯¹è±¡ã€‚ç ”ç©¶æ–¹æ³•æ˜¯æ”¶é›†èµ„æ–™æ³•ä¸Žç»Ÿè®¡åˆ†æžæ³•ã€‚ç ”ç©¶ç»“æžœæ˜¾ç¤ºï¼Œå¤–æ¥è¯ä½¿ç”¨çš„åˆ›é€ æ–¹æ³•æœ‰éŸ³è¯‘ã€éŸ³è¯‘å…¼æ„è¯‘å’Œæ„è¯‘æ–¹æ³•ï¼Œç”¨äºŽç¿»è¯‘326ä¸ªè¡¨ç¤ºäººåã€åœ°åã€å»ºç‘åã€ç¨»è‰åã€ä¼ ç»Ÿä¹ ä¿—åç§°ã€ä¹å™¨ååŠæœ¯è¯ã€‚éŸ³è¯‘æ–¹æ³•æ˜¯æœ€å¸¸ç”¨çš„åˆ›é€ æ–¹æ³•ã€‚æœ€åŽæœ¬æ–‡å¾—å‡ºã€Šå¤ç”¸æ—¥æŠ¥ã€‹éŸ³è¯‘å¤–æ¥è¯çš„éŸ³ç´ è½¬æ¢çš„åˆ†æžç»“æžœã€‚ å…³é”®è¯ ï¼šã€Šå¤ç”¸æ—¥æŠ¥ã€‹ï¼›å¤–æ¥è¯ï¼›åˆ›é€ æ–¹æ³•ï¼›éŸ³ç´ è½¬æ¢ Â  Abstract :This research aims to give reference and as the pioneer research about loan chinese words that come from Bahasa.The object of this research is loan chinese words in Kundian Ribao from September 2013 to February 2014 edition.Â  The result of this research shows 326 loan chinese words in Kundian Ribao using phoneme translation, phonem and meaning translation and meaning translation that imply a personâ€™s name, place, building, paddyâ€™s type, musical instrument, traditional custom and terms. The phoneme translation is the most often used. And the last, the writer conclude the result of analysis about the rule of phoneme conversion in loan chinese words. Keywords: Kundian Ribao, Loan words,Creating Methods,Phoneme Conversion